Possible association between lesions of endodontic origin, infectogenomics and myocarditis - FM Abenavoli; AD Inchingolo; G Dipalma; F Inchingolo (Journal of Dental Problems and Solutions - Peertechz Publications, 2019)
Periodontal disease are chronic infectious disease in which bacteria initiate the host immune response determining at the end of a more or less time damage for tooth. In periodontitis, the clinical findings of bone resorption and loss of clinical attachment level around tooth are a result of inflammatory mediated alterations to the bone remodeling balance. The inflammatory infiltrate present between the plaque biofilm, bone and connective tissues regulate the host immune response to the bacteria.